MPLS fundamentals : LiveLessons (Pearson, 2017)
"MPLS is a key technology for service providers and large enterprises seeking to streamline network management, improve scalability, and simplify migration to newer designs. The MPLS Fundamentals LiveLessons video training course offers more than 7 hours of expert instruction on MPLS network protocols, services, deployment, and operation. Presented by a Cisco technical leader who provides advanced MPLS support to leading service providers, MPLS Fundamentals LiveLessons provides a strong foundation of knowledge for working with MPLS in any environment. Luc De Ghein explains how and why MPLS works, covering MPLS advantages, architecture, protocols, packet forwarding, VPNs, traffic engineering, segment routing, QoS, troubleshooting, and more. De Ghein’s 11 well-organized lessons and more than 40 concise sublessons explore real examples, sample output, and easy-to-follow concept teaching and demos. This is the perfect course to learn MPLS from the ground up, or to supplement your existing knowledge with the most up-to-date training available from the world’s foremost MPLS expert. Whatever your role in running MPLS networks, MPLS Fundamentals LiveLessons will help you get the results you’re looking for."--Resource description page.